2016
DOI: 10.1111/jch.12777
|View full text |Cite
|
Sign up to set email alerts
|

Fruit and Vegetables Consumption and Risk of Hypertension: A Meta‐Analysis

Abstract: The association between fruit and vegetables (FVs) consumption and hypertension risk remains controversial. A systematic search was performed in PubMed and the Web of Science for relevant articles published in English or Chinese up to April 2015. A total of 25 studies with 334,468 patients (41,713 cases) were included in the present meta-analysis. When comparing the highest with the lowest consumption, the pooled relative risks of hypertension were 0.812 (95% confidence interval, 0.740-0.890) for FVs, 0.732 (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(103 citation statements)
references
References 37 publications
10
86
5
2
Order By: Relevance
“…Daily consumption of at least one serving of fruits/vegetables was associated with decreased odds for high BP. This finding is in agreement with other studies . However, we did not find associations with economic indicators and most of other behavioral factors, despite being established risk factors to high BP.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Daily consumption of at least one serving of fruits/vegetables was associated with decreased odds for high BP. This finding is in agreement with other studies . However, we did not find associations with economic indicators and most of other behavioral factors, despite being established risk factors to high BP.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence of high BP increased across age groups among males ( Figure 2). The overall prevalence of pre-hypertension was 29% (95% CI: [26][27][28][29][30][31]) and that of hypertension was 11% (95% CI: 10-13). The prevalence of pre-hypertension among adolescents (12-19 years old) was 24% (95% CI: [22][23][24][25][26][27] and that of young adults (20-24 years old) was 38% (95% CI:…”
Section: Prevalence Of Pre-hypertension and Hypertensionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been suggested that intracellular potassium reduction is compensated for by elevated sodium levels and, as a consequence, blood pressure elevation [87]. In this context, studies have showed that a higher intake of fruit, vegetables [88,89,90], and some specific nutrients (i.e., potassium and magnesium) [91,92,93] are associated with a lower hypertension risk. However, there are no studies evaluating the effect of specific dietary interventions correcting low-grade metabolic acidosis on the hypertension risk.…”
Section: Discussionmentioning
confidence: 99%
“…In this study all groups were encouraged to reduce discretionary foods and it appears this advice was followed. A significant finding, however, was that the addition of walnuts in the IW group appeared to aid in increased consumption of vegetables, low fat milk and yoghurt, and less protein rich foods than the I and C groups, which may in itself have advantages [82][83][84][85].…”
Section: Changes In Food Choicesmentioning
confidence: 60%